PWE-286 Neo-adjuvant chemo-dxt and elapr: the gold standard in the treatment of low rectal cancer. (22nd June 2015) - Miah, A; Boyle, K; Miller, A; Hemingway, D
Abstract : Introduction: The abdomino-perineal resection of the rectum (APR) was first described in detail, by the eminent English surgeon Sir Ernest Miles in his seminal paper in 1908. He described the steps employed to surgically treat low rectal cancers, which were not amenable to Anterior Resection of the rectum. This operation has been the standard treatment for low rectal cancers for over a hundred years. However, despite the advent of TME, local recurrence and survival have not improved to the same degree as seen in Anterior Resection of rectum. Differences in outcomes were partly related to the anatomical and surgical (technical) challenges operating deep in the pelvis. In recent years, the Extra-Levator APR technique has been shown to improve outcome. In this study we report on the differences in outcome following adoption of Chemo-DXT and ELAPR in our unit. Method: We used our colorectal cancer database to select cases that qualified i.e. low rectal cancers that underwent APR in a 3 year period. In hospital Radiology and Pathology IT systems were used to collect further data. We compared various measures including circumferential resection margins (CRM). Margin positivity was compared from the pre ELAPR era to that observed in current unit practice of ELAPR. Results: 1. Our findings showed that neoadjuvant treatment downstaged and in some cases "cured" the tumours prior to surgery, radiologically . 2. With Neoadjuvant Chemo-DXT all T4 tumours were shrunk to a lower ypT stage in our Post-ELAPR data. 3. CRM margin positivity had reduced to 9% since the adoption of ELAPR in the unit. Previously it was 20%; thus, an 11% improvement on the previous audit figure or a >50% reduction in CRM positivity . Conclusion: Our data supports the notion that Neoadjuvant Chemo-DXT and ELAPR can reduce CRM positivity in low rectal cancer and improve prognosis and should form the gold standard treatment of low rectal cancer. Disclosure of interest: None Declared. References: Miles WE. A method of performing abdomino-perineal excision for carcinoma of the rectum and of the terminal portion of the pelvic colon (1908). CA Cancer J Clin. 1971;21(6):361–364 Heald RJ. The 'Holy Plane' of rectal surgery. J R Soc Med . 1988;81(9):503–508 Palmer G, et al . Local control and survival after extralevator abdominoperineal excision for locally advanced or low rectal cancer. Colorectal Dis . 2014;16(7): 527–532